2016
DOI: 10.3892/ol.2016.4711
|View full text |Cite
|
Sign up to set email alerts
|

FOXL2 molecular status in adult granulosa cell tumors of the ovary: A study of primary and metastatic cases

Abstract: Abstract. Granulosa cell tumors (GCTs) of the ovary are uncommon neoplasms, accounting for ~5% of all malignant ovarian tumors. GCTs are a relatively homogeneous group of tumors, categorized into two distinct subtypes, juvenile GCT and adult GCT (AGCT), likely arising from a limited set of molecular events usually involving the disruption of pathways that regulate granulosa cell proliferation. In the present study, the presence of forkheadbox L2 (FOXL2) c.402C>G mutation was investigated in a series of 42 samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…D'Angelo et al reported that the group with more frequent expression of wild‐type FOXL2 has different sex‐cord components (thecoma, luteinized thecoma, Sertoli‐Leydig and sex‐cord tumor with annular tubules) compared with the group with mutated FOXL2 , but no difference was found in the prognosis between the two groups. Zannoni et al reported FOXL2 mutations in 89.2% (33/37) of primary AGCT and that four wild‐type tumors presented with a high Ki‐67 index. A high mitotic index in AGCT is generally associated with worse prognosis, and previously reported aggressive AGCT also had a high mitotic index, as high as 25/10 HPFs…”
Section: Discussionmentioning
confidence: 99%
“…D'Angelo et al reported that the group with more frequent expression of wild‐type FOXL2 has different sex‐cord components (thecoma, luteinized thecoma, Sertoli‐Leydig and sex‐cord tumor with annular tubules) compared with the group with mutated FOXL2 , but no difference was found in the prognosis between the two groups. Zannoni et al reported FOXL2 mutations in 89.2% (33/37) of primary AGCT and that four wild‐type tumors presented with a high Ki‐67 index. A high mitotic index in AGCT is generally associated with worse prognosis, and previously reported aggressive AGCT also had a high mitotic index, as high as 25/10 HPFs…”
Section: Discussionmentioning
confidence: 99%
“…Regarding prognosis, two studies found no difference in tumour stage between AGCTs with FOXL2 mutation and those without FOXL2 mutation . Tumour recurrence has been reported in a small number of AGCTs without FOXL2 mutation . Two studies reported that the rate of recurrence/metastasis was not different between AGCTs with FOXL2 mutation and those without FOXL2 mutation, nor was there a difference in overall survival between AGCTs with FOXL2 mutation and those without FOXL2 mutation in two studies .…”
Section: Agct and Foxl2mentioning
confidence: 91%
“…First, the collective body of literature on AGCT outcome and management has been based on cases defined by morphology (in some cases supported by immunophenotype). Second, as discussed earlier, it is expected that a small percentage of classic‐appearing AGCTs will not harbour FOXL2 mutation, but may still recur or metastasise . Third, FOXL2 mutation status is not associated with tumour stage, recurrence or overall survival in morphologically classic AGCT .…”
Section: Agct and Foxl2mentioning
confidence: 94%
See 2 more Smart Citations